Religious activity, risk-taking preferences and financial behaviour: Empirical evidence from German survey data - Anja Köbrich Leon; Christian Pfeifer (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
Individual preferences with respect to risk taking play an important role in financial economic behaviour and, hence, in financial markets. Using German microdata, we argue that individual religiosity is a determinant of household willingness to take risks, since it shapes relevant individual values and norms. Controlling for overall level of general risk assessment, firstly, we find that different religious affiliations are associated with distinct financial risk-taking attitudes. Adherents to the two main Christian religions in Germany (Protestants and Catholics) are less risk-tolerant in general, but not in financial concerns. The same holds for Muslims. Further, religious involvement is associated with higher risk aversion. Secondly, we examine the extent to which religion-induced heterogeneity in risk-taking preferences actually influences investment decisions of individuals in Germany. We provide evidence suggesting that religious beliefs and religious involvement influence individual portfolio decisions.
Keywords: D14; G11; Z12; 330; church; religion; risk aversion; portfolio choice